Ecclesiastical terms in Rumanian and their semantic implications. - Hatzfeld, Helmut (Thesavrvs, 2023)
It is the title of one of the famous books written by the Rev. Padre Restrepo, called El alma de las palabras, which has impelled me to write something about his preferred topic. I try to use for this purpose material not so well known to Romance scholars mostly concerned with the Western Romanía.